"Less is Better" Philosophy Decreases Home Health Aide Utilization to Increase Reimbursement in Medicare Home Health. Issue 2 (May 2020) - Cabin, William
There has been a 75% decline in home health aide visits between 2000 and 2016, the only Medicare home health nonskilled service. A literature review indicates no studies addressing reasons for the decrease. This study summarizes interviews of nine executives from three for-profit chain-owned Medicare-certified home health agencies. Results indicate agreement on three themes: Medicare home health uses a medical model, focusing on intermittent skilled care; the Medicare home health prospective payment system exacerbated the focus on skilled care by rewarding higher reimbursement for skilled care–based episodes; and a "less is better" synergy has evolved regarding utilization of home health aide services and reimbursement. Policymakers are urged to use the forthcoming Medicare home health Patient-Driven Groupings Model Reform and recent Medicare Advantage changes covering nonmedical services to encourage greater utilization of home health aides and other nonmedical services addressing patient and caregiver social needs affecting care.